Inversion of Riesz Potentials for Dunkl Transform - Moyi Liu; Futao Song; Rongxin Wang (Journal of Function Spaces)
The inversion of Riesz potentials for Dunkl transform when G=Z2d is given by using the generalized wavelet transforms. It is also proved that the Riesz potentials Iακ are automorphisms on the Semyanistyi-Lizorkin spaces.